ESTIMATION OF CARBON RESERVED IN MANGROVE FOREST OF SUNGAI SEMBILAN SUB-DISTRICT, DUMAI CITY, RIAU PROVINCE - Handoyo, Edi; Amin, Bintal; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
Increasing CO2 concentration in the atmosphere is one of the factor which cause global warming. CO2 sequestration through mangrove forests is believed to be one of the efforts to reduce CO2 in atmosphere. This research was conducted in July 2019, aimed at estimating mangrove biomass, mangrove carbon stocks, soil organic carbon, and CO2 sequestration in mangrove forests in the coastal areas of Sungai Sembilan District, Dumai City, Riau Province. This research was conducted using the line transect plot method. Sampling is done by nondestructive sampling by measuring DBH (Diameter at Breast Height) of mangrove trees, and soil sampling is done in a composite manner in each plot. Mangrove biomass calculations done using allometric equations. Then, biomass is converted to carbon stock and CO2 sequestration, where the percentage value of carbon was 0.47 of biomass. As for the organic soil carbon calculation is done by multiplying the bulk density values, the percentage value of 0.47 and a depth of soil carbon. The results showed that the average estimated amount of mangrove biomass, mangrove carbon stocks, soil carbon stocks and CO2 sequestration were 621.46 tons/ha, 289.22 tons/ha, 1819.31 tons/ha and 1074.99 tons/ha. ANOVA analysis results showed that the amount of mangrove biomass, mangrove carbon stock, soil carbon stock and CO2 sequestration between stations were not significantly different (p> 0.05).